THE INFLUENCE OF WEBSITE DESIGN QUALITY, PERCEIVED VALUE AND E-TRUST ON REPURCHASE INTENTION ON E-COMMERCE BEAUTY HAUL - Iskandar, Ivana; Bernarto, Innocentius (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze the positive influence of website design quality, perceived value, e-trust on repurchase intention in e-commerce Beauty Haul. The sampling technique in this research is convenience sampling. The number of samples collected using a questionnaire instrument in the form of google forms is 191 Beauty Haul consumers who have made transactions on the Beauty Haul website more than 2 (two) times. The data were analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM) approach. The results showed that there was a positive influence between all independent variables, namely website design quality, perceived value, e-trust on the dependent variable of repurchase intention. Keywords: Website design quality, perceived value, e-trust, repurchase intention, e-commerce.